(2673) Proposal to conserve the name Verbena fluminensis (Bouchea fluminensis) against V. pseudogervao (Duranteae, Verbenaceae) - Moroni, Pablo Daniel (2019)
For the sake of nomenclatural stability in accordance with Art. 14.2 of the ICN, we believe it would be best to retain the well-known epithet of Verbena fluminensis against that of the rather obscure name V. pseudogervao, which has been subsumed in synonymy since Moldenke´s publication of Bouchea fluminensis in 1940. Acceptance of this proposal would prevent a name (i.e., B. pseudogervao) that has fallen into obscurity for over 75 years from becoming, for purely nomenclatural reasons, the correct name for the economically significant species currently widely known as B. fluminensis.